2019
DOI: 10.1002/chem.201901692
|View full text |Cite
|
Sign up to set email alerts
|

A Sterically Overcrowded, Isopropyl‐Substituted, Lanthanide‐Chelating Tag for Protein Pseudocontact Shift NMR Spectroscopy: Synthesis of its Macrocyclic Scaffold and Benchmarking on Ubiquitin S57 C and hCA II S166 C

Abstract: A sterically overcrowded lanthanide‐chelating tag has been synthesized in order to investigate the influence on the obtained pseudocontact shifts and the anisotropic part of the magnetic susceptibility tensor compared to those of its predecessor DOTA‐M8‐(4R,4S)‐SSPy. For the first time, a concise synthetic route is presented for isopropyl‐substituted cyclen, the macrocyclic scaffold of the lanthanide‐chelating tag, delivering the macrocycle in an overall yield of 6 % over 11 steps. The geometry of the lutetium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…As a next step in the development of the DOTA-M8 tags, an LCT with isopropyl substituents on the basic ring scaffold (Ln-P4M4-DOTA) was synthesized and tested with several protein mutants [148]. Since the 1D spectrum shows a similar shift range as the one of DOTA-M8-(4R4S)-SSPy, the donor atoms were shown by DFT calculations to have a positional deviation of only 0.11 Å when compared to its eight-fold methyl-substituted predecessor and the metal centre mobility was shown by the proposed methodology of Suturina et al [143,149] to correspond to its predecessor, it can be concluded that the enhancement of the PCSs by a factor of almost 2 can be most likely attributed to a more hindered rotation of the LCT on the proteins surface caused by the isopropyl substituents on the basic ring scaffold.…”
Section: Dota-based Lanthanide Chelating Tagsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a next step in the development of the DOTA-M8 tags, an LCT with isopropyl substituents on the basic ring scaffold (Ln-P4M4-DOTA) was synthesized and tested with several protein mutants [148]. Since the 1D spectrum shows a similar shift range as the one of DOTA-M8-(4R4S)-SSPy, the donor atoms were shown by DFT calculations to have a positional deviation of only 0.11 Å when compared to its eight-fold methyl-substituted predecessor and the metal centre mobility was shown by the proposed methodology of Suturina et al [143,149] to correspond to its predecessor, it can be concluded that the enhancement of the PCSs by a factor of almost 2 can be most likely attributed to a more hindered rotation of the LCT on the proteins surface caused by the isopropyl substituents on the basic ring scaffold.…”
Section: Dota-based Lanthanide Chelating Tagsmentioning
confidence: 99%
“…In order to transfer this large intrinsic anisotropy to the protein, motional and rotational averaging of the LCT on the protein has to be suppressed or at least reduced. This was successfully achieved using two-armed LCTs [145,146] as well as by using large substituents on the basic cyclen ring [148] or on the side-arms of the chelator [63]. In the latter two examples, the large substituents effectively decrease the rotational averaging on the proteins surface.…”
Section: Parameters In the Design Of Lctsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 As shown by Joss et al, introduction of even more bulkier isopropyl substituents on the backbone of the LCT can significantly enhance the tensor parameters when compared to its methyl substituted predecessor. 24 In order to circumvent the inherent instability of disulphide linkers towards a reductive environment, various pyridinesulphone-and iodoacetamide linkers have recently been developed. Therefore, we envisioned to synthesize a lanthanide chelating tag offering the combination of a rigidified backbone and a reductively-stable linker ( Fig.…”
mentioning
confidence: 99%
“…The resulting thioether linkage is stable under reductive conditions and has been demonstrated to allow for observation of PCS and RDC in intact eukaryotic cells. 2,3 In order to synthesize the newly designed tags, we combined the synthetic approaches by Joss et al (isopropyl-substituted backbone) 24 and Müntener et al (thiazolo linker) 18 and developed them further to yield the target molecule.…”
mentioning
confidence: 99%